Landscape preference and human well-being - Maulan, Suhardi; Mohd. Shariff, Mustafa Kamal; Miller, Patrick A. (Faculty of Design & Architecture, Universiti Putra Malaysia, 2006)
Humans have always been fascinated by the landscape. Aspects of the landscape that are intriguing play an important role in people’s preferences for landscapes. Since classical times philosophers such as Plato and Socrates, have made inquiries about aesthetics; and numerous theories have emerged. These theories can be categorized into two paradigms. Even though both paradigms focus on the role of landscape in determining landscape preferences one group believes that the aesthetic qualities of a landscape are inherent in the landscape, the other argues that landscape aesthetics lies in people’s cognition or mental understanding of the landscape. However, beginning with the seminal work of Kevin Lynch’s The Image of the City (1960) and his classification of landscape elements that are important to the imageability of urban landscapes, attention has been given to the later paradigm that emphasizes the role of human evolution and cognition in shaping landscape preferences and thus aesthetics. However, this paper argues that, after several decades, no central theory related to landscape preference or aesthetics has emerged, even though many researchers who subscribe to the later paradigm based their theory on the same assumption; human well-being. Therefore, the recognition of the relationship between landscape preference and human well-being should be redeveloped and strengthened by bringing in new evidence.